Membrane Bioreactor for the treatment of natural rubber wastewater - Sulaiman, N.M.N.; Ibrahim, S.; Abdullah, S.L. (Inderscience, 2010)
A membrane bioreactor was set up using two pieces of Kubota flat sheet membranes, with nominal pore size of 0.4 ∝m and a total effective area of 0.2 m²atex concentrate processing factory. A steady-state MLSS concentration was attained at 8500 mg/L during biomass acclimatisation. A critical flux of 0.01224 m³/m²h was determined using the flux step method, whereas an optimum operating flux for fouling minimisation was determined from the sub-critical flux region, to be 0.009 m³/m²h at a COD loading of 3500 mg/L. The BOD3 and COD removal efficiencies were 96.78% and 96.99%, respectively.